2005
DOI: 10.1007/s00425-005-0119-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of anomalous chloroplasts in transgenic ipt tobacco

Abstract: Anomalies in the ultrastructure of chloroplasts, from transgenic ipt tobacco, overproducing endogenous cytokinins (CKs) were studied. Detailed analyses of CKs and their metabolites showed that Pssu-ipt tobacco contained enhanced contents of CKs both in leaves and in isolated chloroplasts. The role of CKs in the formation of anomalous structures is suggested. Pssu-ipt chloroplasts frequently formed the distinct peripheral reticulum with a system of caverns that often involved mitochondria and/or peroxisomes. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Previous studies have also observed changes to chloroplast structure following exposure to elevated cytokinins. For example, the formation of crystalloids or an ‘amoeboid-like’ morphology is characteristic of plastids in the leaves of stable transgenic tobacco overexpressing cytokinin synthesis genes [34,40]. Although we never observed crystalloids, the description of the ‘amoeboid-like’ plastid structure is reminiscent of our observations of multiple stromules emanating from a single plastid body.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have also observed changes to chloroplast structure following exposure to elevated cytokinins. For example, the formation of crystalloids or an ‘amoeboid-like’ morphology is characteristic of plastids in the leaves of stable transgenic tobacco overexpressing cytokinin synthesis genes [34,40]. Although we never observed crystalloids, the description of the ‘amoeboid-like’ plastid structure is reminiscent of our observations of multiple stromules emanating from a single plastid body.…”
Section: Discussionmentioning
confidence: 65%
“…On the contrary these plant hormones positively correlated with AR regeneration/final production effectiveness. Similarly, the presence of various anomalies in the ultrastructure of chloroplasts, from transgenic tobacco was the result of overproduction of endogenous CKs (Synkova et al 2006). Surprisingly, after LT the same type of CKs positively correlated with GR regeneration/final production, whereas trans isomers of Z and ZR seems to have positive effect on AR regeneration/final production effectiveness.…”
Section: Discussionmentioning
confidence: 95%
“…Chl levels were also decreased in the shoot of the B-type arr1 arr10 arr12 triple mutant, affected in the majority of cytokininactivated responses during vegetative plant development (Argyros et al, 2008;Ishida et al, 2008). In addition, ectopic expression of the bacterial cytokinin biosynthetic ISOPENTENYLTRANSFERASE (ipt) gene increased Chl levels, enhanced photosynthetic activity, affected the ultrastructure of chloroplasts, and delayed leaf senescence (Synková et al, 2006;Procházková et al, 2008;Cortleven and Valcke, 2012).…”
mentioning
confidence: 99%